Pembuatan Laporan Keuangan Sederhana dan Pemanfaatan Marketplace Sebagai Sarana Penjualan Produk UMKM - Juitania Juitania; I Gede Adi Indrawan; Raden Ai Lutfi Hidayat; Andri Sjahputra; Suharna Suharna (Universitas Pamulang, 2020)
Pengabdian kepada Masyarakat (PKM) is in collaboration with the Rumah Pemberdayaan Masyarakat (RPM) Institute of South Tangerang. RPM classifies micro small medium enterprises based on the length of the trading business and the minimum turnover. The type of trading with a minimum business category of 2 years with a minimum turnover of five million in one month, is classified as the small-medium enterprise scale-up category. The small-medium enterprise must truly compete not only in terms of marketing but also in terms of financial management readiness. Weak awareness of the importance of the discipline of bookkeeping or financial management is still a serious matter among micro small medium enterprise businessmen and businesswomen in South Tangerang. The hectic production and marketing activities and lack of information regarding good financial and according to applicable standards (SAK-EMKM) have made micro small-medium enterprise players neglect the recording of their economic transactions. There is a need for counselling and assistance regarding the financial standards that apply to micro small medium enterprises (SAK-EMKM) as well as the easiest way to assist financial management. In addition, micro small-medium enterprise players still have inadequate knowledge about the benefits of using a marketplace as a forum for the promotion and sale of their business products. The purpose of Pengabdian kepada Masyarakat is to help MSME players in making simple financial reports in accordance with SAK-EMKM, as well as helping micro small medium enterprise businessmen and businesswomen increase sales of their products by maximizing the promotion and sales features of the marketplace. The implementation of the workshop is Group-based activities that are carried out comprehensively in relation to applicable MSME standards and provide training in the preparation of financial reports and marketplace management. PkM results from 20 MSME participants who re-registered, as many as 18 participants were suitable and disciplined in keeping records of their business transactions and managing marketplace accounts of MSME players for a period of 3 months. It is hoped that this PkM can be useful for various parties including MSME businessmen and businesswomen themselves, the Indonesian Accountants Association, the Government and academics.